Preclinical models of mitochondrial dysfunction: mtDNA and nuclear-encoded regulators in diverse pathologies - Miller, Dalia M.; Archer, Stephen L.; Dunham-Snary, Kimberly J. (Frontiers in Aging, 2025)
Mitochondrial-driven diseases encompass a diverse group of single-gene and complex disorders, all linked to mitochondrial dysfunction, with significant impacts on human health. While there are rare mitochondrial diseases in which the primary defect resides in mutations in mitochondrial DNA, it is increasingly clear that acquired mitochondrial dysfunction, both genetically- and epigenetically-mediated, complicates common complex diseases, including diabetes, cardiovascular disease and ischemia reperfusion injury, cancer, pulmonary hypertension, and neurodegenerative diseases. It is also recognized that mitochondrial abnormalities not only act by altering metabolism but, through effects on mitochondrial dynamics, can regulate numerous cellular processes including intracellular calcium handling, cell proliferation, apoptosis and quality control. This review examines the crucial role of preclinical models in advancing our understanding of mitochondrial genetic contributions to these conditions. It follows the evolution of models of mitochondrial-driven diseases, from earlier in vitro and in vivo systems to the use of more innovative approaches, such as CRISPR-based gene editing and mitochondrial replacement therapies. By assessing both the strengths and limitations of these models, we highlight their contributions to uncovering disease mechanisms, identifying therapeutic targets, and facilitating novel discoveries. Challenges in translating preclinical findings into clinical applications are also addressed, along with strategies to enhance the accuracy and relevance of these models. This review outlines the current state of the field, the future trajectory of mitochondrial disease modeling, and its potential impact on patient care.